Strategi Pemenangan Partai PDIP dalam Pemilu Legislatif Tahun 2024 - Lia, Lapina; Wahyiah, Ita Rosita; Sam, Maulana Suprihatin; Cintana, Dea; Mita, Nindi Merliana; Ningsih, Tawwafaona (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2024)
The 2024 Legislative Election in Indonesia marks a crucial period for the Indonesian Democratic Party of Struggle (PDIP) in maintaining and enhancing its political strength. In this context, this journal analyzes the winning strategies adopted by the PDIP in facing this election. This research employs an analytical approach by examining the strategies implemented by the PDIP from various dimensions, including political campaigns, resource management, and the use of social media. The analysis results indicate that the PDIP combines a holistic and targeted approach, strengthening its traditional voter base while striving to attract new voters